Characterization of a Plant Nuclear Matrix Constituent Protein in Liverwort - Wang, Nan; Karaaslan, Ezgi Süheyla; Faiss, Natalie; Berendzen, Kenneth Wayne; Liu, Chang (Frontiers in Plant Science, 2021)
The nuclear lamina (NL) is a complex network of nuclear lamins and lamin-associated nuclear membrane proteins, which scaffold the nucleus to maintain structural integrity. In animals, type V intermediate filaments are the main constituents of NL. Plant genomes do not encode any homologs of these intermediate filaments, yet plant nuclei contain lamina-like structures are present in their nuclei. In Arabidopsis thaliana, CROWDED NUCLEI (CRWN), which are required for maintaining structural integrity of the nucleus and specific perinuclear chromatin anchoring, are strong candidates for plant lamin proteins. Recent studies revealed additional roles of Arabidopsis Nuclear Matrix Constituent Proteins (NMCPs) in modulating plants’ response to pathogen and abiotic stresses. However, detailed analyses of Arabidopsis NMCP activities are challenging due to the presence of multiple homologs and their functional redundancy. In this study, we investigated the sole NMCP gene in the liverwort Marchantia polymorpha (MpNMCP). We found that MpNMCP proteins preferentially were localized to the nuclear periphery. Using CRISPR-Cas9 techniques, we generated an MpNMCP loss-of-function mutant, which displayed reduced growth rate and curly thallus lobes. At an organelle level, MpNMCP mutants did not show any alteration in nuclear morphology. Transcriptome analyses indicated that MpNMCP was involved in regulating biotic and abiotic stress responses. Additionally, a highly repetitive genomic region on the male sex chromosome, which was preferentially tethered at the nuclear periphery in wild-type thalli, decondensed in the MpNMCP mutants and located in the nuclear interior. This perinuclear chromatin anchoring, however, was not directly controlled by MpNMCP. Altogether, our results unveiled that NMCP in plants have conserved functions in modulating stress responses.